Research on Searching for Optimal Frequency of Variable Frequency Charging Technology - Tiezhou, Wu; Zilong, Li; Liping, Hu; Ting, Bai (Recent Advances in Electrical & Electronic Engineering, 2014)
This paper presents a searching method for optimal frequency of variable frequency pulse charging. Based on the analysis of the characteristics of the battery impedance, we give charging frequency a positive and reverse disturbance to make it form a hysteresis loop. Variations of current were recorded before and after the two disturbances. According to the frequency disturbance rules based on the hysteresis loop, we determine whether it is the optimal frequency. Otherwise, we continue the new round of disturbances until the operating point frequency is fixed at the optimal frequency. This method can dynamically search for the optimal frequency in charging to improve the energy transfer efficiency, significantly shortening the battery charging time. Experiments show that under the same conditions, the charging rate is increased by 28% compared with the traditional way of charging with constant current and constant voltage, and increased by 15% compared with the fixed frequency charging mode.
Keywords: optimal charging frequency